2018
DOI: 10.1371/journal.pone.0194028
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of home delivery amongst HIV-infected women attending care at a rural public health facility in Coastal Kenya

Abstract: BackgroundHome delivery, referring to pregnant women giving birth in the absence of a skilled birth attendant, is a significant contributor to maternal mortality, and is encouragingly reported to be on a decline in the general population in resource limited settings. However, much less is known about home delivery amongst HIV-infected women in sub-Saharan Africa (sSA). We described the prevalence and correlates of home delivery among HIV-infected women attending care at a rural public health facility in Kilifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
1
13
3
Order By: Relevance
“…Further, our findings show that the proportion of facility-based deliveries has increased over time, which is consistent with several other studies in this setting [ 20 , 21 ]. This is likely related to the government of Kenya’s policy on free maternity services that was rolled out in June 2013.…”
Section: Main Textsupporting
confidence: 93%
“…Further, our findings show that the proportion of facility-based deliveries has increased over time, which is consistent with several other studies in this setting [ 20 , 21 ]. This is likely related to the government of Kenya’s policy on free maternity services that was rolled out in June 2013.…”
Section: Main Textsupporting
confidence: 93%
“…The study also reflected the importance of education in maternal health service use. The less educated a woman becomes, the higher her chances of having non-facility delivery [28][29][30][31][32]. Well educated women are more often than not exposed to vital information about health care utilization, including facility delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Sub-Saharan Africa and South Asia together contribute over 85% of maternal deaths, and of which only half of deliveries are institutional [ 6 ]. Previous studies across the sub-Saharan Africa report a significant proportion of mothers still deliver at home [ 8 10 ]. Furthermore, a cross-sectional study conducted in Abobo District showed that significant number of women (91.5%) had given birth at home [ 11 ].…”
Section: Introductionmentioning
confidence: 99%